Effects of inactivation or overexpression of the sspF gene on properties of Bacillus subtilis spores. - Loshon, C A (1997)
Inactivation of the Bacillus subtilis sspF gene had no effect on sporulation, spore resistance, or germination in a wild-type strain or one lacking DNA protective alpha/beta-type small, acid-soluble proteins (SASP). Overexpression of SspF in wild-type spores or in spores lacking major alpha/beta-type SASP (alpha- beta- spores) had no effect on sporulation but slowed spore outgrowth and restored a small amount of UV and heat resistance to alpha- beta- spores. In vitro analyses showed that SspF is a DNA binding protein and is cleaved by the SASP-specific protease (GPR) at a site similar to that cleaved in alpha/beta-type SASP. SspF was also degraded during spore germination and outgrowth, and this degradation was initiated by GPR.